Hodnocení finanční situace podniku a návrhy na její zlepšení - Požárová, Veronika (Vysoké učení technické v Brně. Fakulta podnikatelská, 2011)
Diplomová práce se zabývá analýzou finanční situace společnosti Focus Cz Marketing - and IT Research s. r.o. v období 2004 – 2007 pomocí vybraných metod finanční analýzy. Určuje silné a slabé stránky, nedostatky a příležitosti společnosti Focus Cz Marketing - and IT Research s. r.o. a navrhuje možná řešení, která mají vést ke zlepšení finanční situace této společnosti v budoucnu.

Master´s Thesis describes analysis of the financial situation company Focus Cz Marketing - and IT Research Ltd. in period 2004 – 2007 through the chosen methods. It diagnose strong and weak sides, deficiencies and opportunities of the company Focus Cz Marketing - and IT Research Ltd. and propose possible solutions, which will lead to improvement of the financial situation for this company in the future.
Evaluation of the Financial Situation in the Firm and Proposals to its Improvement
Keywords: Finanční analýza; rentabilita; investice; účetní výkazy; hodnocení firmy; SWOT analýza.; Financial analysis; profitability; investments; financial statements; company rating; SWOT analysis.